2022
DOI: 10.3390/jfmk7040103
|View full text |Cite
|
Sign up to set email alerts
|

Downhill Sections Are Crucial for Performance in Trail Running Ultramarathons—A Pacing Strategy Analysis

Abstract: Trail running is an increasingly popular discipline, especially over long-distance races (>42.195 km). Pacing strategy, i.e., how athletes modulate running speed for managing their energies during a race, appears to have a significant impact on overall performance. The aims of this study were to investigate whether performance level, terrain (i.e., uphill or downhill) and race stage affect pacing strategy and whether any interactions between these factors are evident. Race data from four race courses, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…It is difficult to establish a connection between pacing variability and ultra-trail performance, as the profile of the race directly influences the mean speed, which has been the main variable used to analyze pacing. However, it might be suggested that this is due to the greater capacity of the high-level runners to adapt their effort to the profile (i.e., uphills and downhills) and race segment (i.e., early, or last part of the race), as previous studies have stated [ 19 ]. In this regard, it is also important to note that the OCC ® is significantly shorter (56.3 km) than the ultra-trails that had been previously analyzed (i.e., >100 km).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to establish a connection between pacing variability and ultra-trail performance, as the profile of the race directly influences the mean speed, which has been the main variable used to analyze pacing. However, it might be suggested that this is due to the greater capacity of the high-level runners to adapt their effort to the profile (i.e., uphills and downhills) and race segment (i.e., early, or last part of the race), as previous studies have stated [ 19 ]. In this regard, it is also important to note that the OCC ® is significantly shorter (56.3 km) than the ultra-trails that had been previously analyzed (i.e., >100 km).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in our study we did not have access to these data. Consequently, a recommendation for non-elite OCC ® participants would be to adapt their pace to the race profile with a slower pace during uphills and a faster pace during downhills [ 19 ]. Further studies considering the participants’ experience are warranted to confirm the validity of this recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggested that, from a performance perspective, the higher running economy may partially compensate for the lower V O 2max in female runners [ 87 ]. However, controversial findings exist on sex differences in fatigue resistance and pacing in road and trail ultra-marathons [ 81 , 88 , 89 ]. Some authors reported greater fatigue resistance and better pacing in female ultra-marathon participants [ 81 , 89 ], whereas others found that women tended to slow down more than men in the later stages of trail running ultra-marathons, despite the terrain (uphill and downhill) [ 88 ].…”
Section: Uphill/downhill Locomotionmentioning
confidence: 99%
“…However, controversial findings exist on sex differences in fatigue resistance and pacing in road and trail ultra-marathons [ 81 , 88 , 89 ]. Some authors reported greater fatigue resistance and better pacing in female ultra-marathon participants [ 81 , 89 ], whereas others found that women tended to slow down more than men in the later stages of trail running ultra-marathons, despite the terrain (uphill and downhill) [ 88 ]. Further studies are needed to better understand sex differences in the energetics and biomechanics of incline walking and running, and fatigue resistance and pacing strategies in ultra-marathons controlling for fitness levels, anthropometric differences, menstrual cycle effect and the level of relative effort used for testing both sexes.…”
Section: Uphill/downhill Locomotionmentioning
confidence: 99%
“…Since the first "Comrades Marathon" in 1921, ultramarathons have experienced meteoric growth [4,5]. As a result, ultrarunning has become increasingly popular and competitive [6,7], with as many as 1,500 runners participating in a single 100-mile race [7]. The majority of athletes that engage in ultramarathons are considered master athletes because they are at least 35 years old and either compete or prepare to compete.…”
Section: Introductionmentioning
confidence: 99%